Effects of Intervention Program for Youth Basketball Players on Three-Point Shooting and Cognitive Ability - Li , Yicong; Leethong-in, Pornteap; Tongdecharoen, Wisute (International Journal of Sociologies and Anthropologies Science Reviews, 2025)
Background and Aim: The proficiency level of the basketball program for students aged 14-16 years at Wuhan Sports School is a significant concern, as there is a noticeable lack of tailored training programs specifically designed for this age group. Therefore, this research aims to improve efficiency in three-point shooting ability, cognitive ability, and specific fitness for youth basketball players. Materials and Methods: This research employed a quasi-experimental design. The population consisted of 128 male youth basketball players aged 14-16 from Wuhan Sports School. Participants were assessed on three-point shooting ability, cognitive ability, and specific fitness. They were then divided into control and experimental groups using systematic sampling. The training intervention was conducted over 8 weeks to improve three-point shooting ability, cognitive ability, and specific fitness, with measurements taken before training, after 4 weeks of training, and after 8 weeks of training. Data analysis included mean, standard deviation, one-way repeated measures ANOVA, and dependent t-tests. The level of statistical significance was set at 0.05. Results: Following 8 weeks of training, statistically significant differences at the 0.05 level were observed in three-point shooting ability, cognitive ability, and sport-specific fitness across pre-test, 4-week training, and post-test measurements. These findings indicate that the developed basketball training program can effectively enhance three-point shooting ability, cognitive ability, and specific fitness. Conclusion: The intervention program improved three-point shooting and cognitive ability for youth basketball players.